Given the function:
![f\mleft(x\mright)=2x^2+5x-8](https://img.qammunity.org/2023/formulas/mathematics/high-school/tt3hz42d2psr6u2b2snpqv4juas78rap5u.png)
We will find the difference quotient for the given function
We will use the following formula:
![(f(x+h)-f(x))/(h),h\\e0](https://img.qammunity.org/2023/formulas/mathematics/high-school/tsvap3hoqc60o5g70f8m4maa8vy08cjbol.png)
so, we will find f(x+h) then find the differnce of f(x+h) and f(x)
![\begin{gathered} f(x+h)=2(x+h)^2+5(x+h)-8 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/cfizj9w6vod9lp4ni9dr5mxhz4kfd4196q.png)
![f(x+h)-f(x)=2(x+h)^2+5(x+h)-8-(2x^2+5x-8)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ge06xq131hpwg3od605d9lzi9oarf56rhc.png)
Expand then simplify
![\begin{gathered} f(x+h)-f(x) \\ =2(x^2+2hx+h^2)+5x+5h-8-2x^2-5x+8 \\ =2x^2+4hx+2h^2+5x+5h-2x^2-5x \\ =(2x^2-2x^2)+(5x-5x)+4hx+5h+2h^2 \\ =4hx+5h+2h^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/jb67way2busbv4ibsq2ackj68gqn9lfj6q.png)
Now, divide the result by (h)
![\begin{gathered} (f(x+h)-f(x))/(h)=(4hx+5h+2h^2)/(h) \\ \\ =(h(4x+5+2h))/(h)=4x+5+2h \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/l4d8z0aar2avntl3z81005g2y0gj5jlm2k.png)
So, the answer will be:
The the difference quotient = 4x + 5 + 2h